2014
DOI: 10.1038/npp.2014.144
|View full text |Cite
|
Sign up to set email alerts
|

A Role Beyond Learning for NMDA Receptors in Reward-Based Decision-Making—a Pharmacological Study Using d-Cycloserine

Abstract: N-methyl-D-aspartate (NMDA) receptors are known to fulfill crucial functions in many forms of learning and plasticity. More recently, biophysical models, however, have suggested an additional role of NMDA receptors in evidence integration for decision-making, going beyond their role in learning. We designed a task to study the role of NMDA receptors in human reward-guided learning and decision-making. Human participants were assigned to receive either 250 mg of the partial NMDA agonist d-cycloserine (n=20) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 36 publications
(36 reference statements)
4
37
0
Order By: Relevance
“…Lower values indicate better fit. On both measures, models using linear integration of magnitude and probability (M1-M3) provided an overwhelmingly better fit, as found previously (Scholl et al, 2014). While the model fit measures do not agree on whether modeling learning with a shared or separate learning rates (α) is best (M1 vs. M2), we note that for the key parameter of interest here, the use of learnt information (γ), we obtain the same value using either model (r = 1.0, p<10 −36 ).…”
Section: Resultssupporting
confidence: 83%
“…Lower values indicate better fit. On both measures, models using linear integration of magnitude and probability (M1-M3) provided an overwhelmingly better fit, as found previously (Scholl et al, 2014). While the model fit measures do not agree on whether modeling learning with a shared or separate learning rates (α) is best (M1 vs. M2), we note that for the key parameter of interest here, the use of learnt information (γ), we obtain the same value using either model (r = 1.0, p<10 −36 ).…”
Section: Resultssupporting
confidence: 83%
“…In humans, results have so far been mixed, with some studies reporting that DCS could enhance motor learning ( Kuriyama et al, 2011 ), fear conditioning ( Kalisch et al, 2009 ) or incremental learning ( Forsyth et al, 2015 ), but others failing to find an effect on motor learning ( Cherry et al, 2014 ; Feld et al, 2013 ; Kuo et al, 2008 ), fear extinction ( Guastella et al, 2007 ; Klumpers et al, 2012 ) or reward learning ( Scholl et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…DCS might exert its clinical effects via learning-independent cognitive mechanisms in which NMDA receptors play a role, such as evidence integration or decision-making ( Floresco et al, 2008 ; Scholl et al, 2014 ; Shen et al, 2010 ; Standage and Pare, 2011 ; Standage et al, 2013 ). In an exploratory analysis of non-learning dependent effects we found that DCS led participants to shift their balance in how quickly and accurately they responded towards more careful responding compared with placebo.…”
Section: Introductionmentioning
confidence: 99%
“…No drug or placebo was administered on the second day. Although the idea of using NMDAR agonists to enhance cognition is not new, past studies examining diverse cognitive domains have yielded mixed results (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Difficulty reconciling divergent effects has limited our ability to harness NMDAR agonists as cognitive enhancers.…”
mentioning
confidence: 99%